Kajian Interaksi Obat Pada Pasien Demam Tifoid di Rumah Sakit X di Surakarta - Eersta Zusvita Widyastuti; Adhi Wardhana Amrullah; Agnes Prawistya Sari; Avianti Eka Dewi Aditya Purwaningsih (Fakultas Farmasi Universitas Setia Budi, 2024)
Salmonella typhi bacteria reside in the human body and cause an infection known as typhoid fever. The number of cases of typhoid fever in Indonesia reaches 81% per 100,000 people. The use of various drugs in the treatment of typhoid fever will increase the possibility of drug interactions. This research is a descriptive observational cross-sectional study. Data from medical records of typhoid fever patients at